Snap strategies for couples : 40 fast fixes for everyday relationship pitfalls - Schwartz, Pepper; Staheli, Lana (Seal Press, a member of the Perseus Books Group, 2015)
Offers quick solutions to the most common relationship problems. Dr. Lana Staheli and Dr. Pepper Schwartz present 40 practical, immediate fixes (or snaps) that partners can use to end the fighting, leave the baggage behind, and move their relationship forward.